The Effect of Jamu on Joint Pain in Medan Sunggal, Indonesia - Eqlima Elfira (Talenta Publisher, 2020)
ABSTRACT Jamu is a traditional medicine with nutritious plants that can reduce joint pain. The purpose of this study was to determine the effectiveness of Jamu to reduce joint pain. This research design uses pre-experimental with one-time case study. The research samples involved ten women with different age groups in consecutive months consuming Jamu. Data analysis using observation sheet VAS (Visual Analog Scale) and binomial test with IBM SPSS 26. The results of the binomial test showed a p-value of .021 < alfa .05 which means that H0 is rejected and H1 is accepted. It’s showed that there is an effect of Jamu on joint pain reduction. The findings of this study found that within three days, the respondents felt changes in their joints and their bodies felt healthier It is concluded that Jamu contains herbs in maintaining health and relieving pain.